Integrasi Peternakan Unggas Dan Budidaya Maggot : Solusi Berkelanjutan Untuk Pengelolaan Limbah Dan Peningkatan Efisiensi Pakan Di Kelompok Tani Ternak Tui Jati - Maslami, Vebera; Dwi Kusuma Purnamasari; Endang Purnama Dewi; Ely Ermawati; Irmanuddin; Ni Made Ayu Yowana; Samsul Mahrip; Sase Nogyran Andry Lia (Universitas Mataram, 2025)
The integration of poultry farming and maggot cultivation was carried out with the Tui Jati Livestock Farmers Group in Central Lombok Regency to enhance farmers' skills in managing poultry waste, maggot cultivation, and improving poultry feed efficiency. The main challenges were the environmental pollution caused by poultry waste and the high cost of feed, which negatively impacts farmers' economy. The program aimed to assist in processing poultry waste into a medium for maggot farming, offering an efficient and sustainable alternative feed, reducing dependence on expensive commercial feed, and mitigating environmental pollution. The program also designed an integrated system for poultry and maggot farming through a processing facility and provided training on poultry waste management and maggot cultivation techniques. The methods included initial observation and mapping of conditions, thematic training on maggot egg hatching and cultivation, hands-on field guidance, and evaluation through pre-tests, post-tests, observations, and interviews. Evaluation results showed an improvement in farmers' knowledge and skills, with average scores rising to a